Analisis Konsumsi Bahan Bakar Truck Mitsubishi Fuso 220 Pada Pengangkutan Batubara Berdasarkan Rimpull (Studi Kasus: PT. Haswi Kencana Indah) - Afni Nelvi (Jurnal Teknik dan Teknologi Tepat Guna, 2023)
PT.Haswi Kencana Indah transported coal from the mining front to the stockpile As far as 798 m with fuel concumption in December 2022 of 21 liter/hours.which has exceeded the company standard of 19 liter/hour.The purpose of this study was to calculate the fuel concumption of the Mitsubishi fuso 220 truck during coal hauling operations and to analyze the fuel concumptions of the Mitsubishi fuso 220 truck based on rimpull calculations. The data needed is how much fuel the Mitsubishi fuso 220 truck uses in coal hauling operations The fuel concumption of the Mitsubishi fuso 220 truck, based on rimpull calculations,is 20,73 liter/hours, with loaded of the Mitsubishi fuso 220 truck is 12.53 liter/hours, the empty is 5,98 liter/ hours, and idle is 2,22 liter/hours.